PENERAPAN STRUKTUR BENTANG LEBAR PADA REDESAIN SASANA LEMBU SWANA BOXING DI TENGGARONG - Mafazah Noviana; Nur Husniah Thamrin; M. Adhitia Leores (Indonesian Society of Applied Science, 2022)
Sport is an activity that is useful to strengthen and nourish our bodies. Boxing is a martial art that predominantly uses both hands as physical contact with the opponent. In this study, a redesign of Sasana Lembu Swana Boxing was carried out in Tenggarong by applying a wide span structure as well as natural ventilation and lighting. The redesign was carried out with the background that the existing condition of the building was no longer suitable for boxing athletes to practice comfortably. The purpose of this research is to redesign the Lembus Swana Boxing gym in Tenggarong by applying a wide span structure and natural ventilation and lighting. With the existence of Sasana Lembu Swana Boxing in Tenggarong, it is hoped that it will produce a comfortable training and competition facility for athletes with a more appropriate and aesthetic building structure, as well as providing natural ventilation and lighting. The method used in this research is the architectural design method starting with processing general data and information from various sources related to the needs and requirements of the redesign of Sasana Lembu Swana Boxing. This research produces a redesigned image of Sasana Lembu Swana Boxing by applying a wide span structure and natural lighting and ventilation.